Problems concept and differences between project, program and portfolio management - Piterska, Varvara; Kramskiy, Sergiy (КНУБА, 2017)
The article examines the essence of management of innovative enterprise project based on a portfolio approach, offers tips on how to create portfolios and discusses the basic mechanisms for managing the innovation portfolio. One of the important factors of the spread of any innovation is its interaction with relevant socio-economic environment, which is an essential element of competing technologies. In article examines problems, examples of development of models of management project portfolios. Methodological aspects program, projects, portfolio management, analyzed existing approaches and models of portfolio management, proposed a system of models for project selection and resource allocation. The review of national and especially foreign portfolio management concepts. The problems of organization and support management in organizations that implement their activities in the form of projects were considered, as well as the main approaches to managing a portfolio of projects, procedures for drawing portfolio, taking into account both formal and informal aspects was proposed. The author's own view on the problem of the formation of programs, the portfolio of projects was realized.
Keywords: project; program; portfolio management; innovative portfolio; project-oriented organization; risk; 005.8; 005.93